Lemierre's syndrome: an evolving disease - Manjunath, Chaitra; Atkins, Amanda; Ilonze, Chibuzo (International Journal of Contemporary Pediatrics, 2023)
Lemierre’s syndrome is characterized by thrombophlebitis of the internal jugular vein with resulting systemic septic emboli. Most cases occur following an oropharyngeal infection and have been historically caused by the bacterial pathogen Fusobacterium necrophorum. However, infection from other pathogens is becoming more common in recent years. Our case is special in the sense that Lemierre’s syndrome was caused by staphylococcus aureus after influenza infection. A 23-month-old male presented with complaints of left neck swelling and recurrent fever for one week, following influenza A infection. The child was ill-appearing with fever, tachycardia, tachypnea, and erythematous swelling on the left cheek. Laboratory results revealed elevated inflammatory markers. Computed tomography (CT) scan of the neck showed loculated fluid collection suggesting an intra parotid abscess with poor visualization of the internal jugular vein (IJV). Blood cultures were positive for methicillin-sensitive Staphylococcus aureus. Due to high clinical suspicion of Lemierre’s syndrome, a doppler ultrasound was obtained which showed a left IJV thrombus. CT scan of the chest after the clinical suspicion showed multiple bilateral pulmonary nodules suggesting septic emboli. He was treated with antibiotics and a six-week course of the anticoagulant with a resolution of his thrombus. Though historically, Lemierre’s disease is caused by Fusobacterium necrophorum, other causative organisms such as methicillin-sensitive Staphylococcus aureus are increasingly being recognized. Lemierre’s disease can present as a complication of influenza. A high index of clinical suspicion based on the location of the abscess helped us delineate diagnostic tests and treatment.